2009
DOI: 10.1128/aac.00610-09
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparumDrug Resistance in Madagascar: Facing the Spread of Unusualpfdhfrandpfmdr-1Haplotypes and the Decrease of Dihydroartemisinin Susceptibility

Abstract: The aim of this study was to provide the first comprehensive spatiotemporal picture of Plasmodium falciparum resistance in various geographic areas in Madagascar. Additional data about the antimalarial resistance in the neighboring islands of the Comoros archipelago were also collected. We assessed the prevalence of pfcrt, pfmdr-1, pfdhfr, and pfdhps mutations and the pfmdr-1 gene copy number in 1,596 P. falciparum isolates collected in 26 health centers ( In recent decades, the emergence and subsequent spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
52
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 42 publications
10
52
2
3
Order By: Relevance
“…It has been observed that P. falciparum infection can persist asymptomatically in semi-immune individuals for more than 18 months when the possibility of reinfection is excluded (14). Similar to the observation of our present study, the persistence of asymptomatic P. falciparum infection interseasonally, in areas with seasonal transmission (15), has been reported in African countries (12,16,17). Such findings have driven presumptive intermittent antimalarial treatment strategies for asymptomatic carriers, regardless of their infection status, to reduce the disease burden in African countries.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been observed that P. falciparum infection can persist asymptomatically in semi-immune individuals for more than 18 months when the possibility of reinfection is excluded (14). Similar to the observation of our present study, the persistence of asymptomatic P. falciparum infection interseasonally, in areas with seasonal transmission (15), has been reported in African countries (12,16,17). Such findings have driven presumptive intermittent antimalarial treatment strategies for asymptomatic carriers, regardless of their infection status, to reduce the disease burden in African countries.…”
Section: Discussionsupporting
confidence: 91%
“…The region of the pfATPase6 gene spanning codon 769 was amplified as described previously (9). A portion of the pfdhfr gene spanning codons 16, 51, 59, 108, and 164 and a portion of the pfdhps gene spanning codons 436, 437, 540, 581, and 613 were amplified by two rounds of PCR using the primers described earlier (11,12).…”
Section: Methodsmentioning
confidence: 99%
“…For each patient with a positive RDT result and after informed consent had been obtained, blood samples either were collected from a finger prick and placed onto filter paper or were collected by venipuncture and placed into EDTA-containing tubes. The patients were then promptly treated according to the national malaria policy with a combination of artemether plus lumefantrine (Coartem; Novartis, Basel, Switzerland) in the Comoros Islands (17) (2). Venous blood samples collected in EDTA-containing tubes were transported to Antananarivo, Madagascar, at ϩ4°C within 24 to 48 h of collection.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies performed in Madagascar have shown that the situation is deteriorating and have demonstrated the introduction of P. falciparum multidrug-resistant parasites into Madagascar from the Comoros Islands (17), the rapid rise in the frequency of P. falciparum parasites with both pfdhfr and dhps mutations, and the alarming emergence of the single pfdhfr 164L allele from isolates collected during the last 3 years (2).…”
mentioning
confidence: 99%
“…Because malaria parasites contain an essential organelle of bacterial origin, the apicoplast, numerous antibacterials kill malaria parasites (1-4) and are commonly used in malaria prophylaxis or as components of multiple drug therapies (5,6). However, the emergence of multiresistant parasites compromises the efficacy of many existing chemotherapies, leading to a growing urgency for the search of new antimalarials (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%